Physics-Based Simulation for Health Management of Rotating Machinery - Walker, Ryan; Perinpanayagam, Suresh; Jennions, Ian K. (Cranfield University, 2011)
Data-driven techniques for diagnosing faults in rotating machinery have a long history. Such approaches undoubtedly have their strengths and much research is still being performed in this area - recently into gearbox and bearing faults in particular. However, with the increasing power and sophistication of simulation tools, new methods for diagnosis, localization and prognosis of faults are rapidly being researched. This paper outlines current developments in modeling and simulation for rotating machinery health management and discusses the potential for such technologies to move from the realm of research into live systems. Comparisons and synergies with traditional data driven methods are made and it is concluded that simulation-driven techniques have much potential for next generation PHM systems.